A Novel Video-Based Patient Education Program to Reduce Penile Prosthetic Surgery Cancellations. Issue 6 (December 2019) - Ballon-Landa, Eric; Clavijo, Raul; Gross, Martin; Tapscott, Ashley; Ramasamy, Ranjith; Bowen, Ashley; Freedman, Sheldon; Wierschem, Michael; Welliver, Charles; Simoncini, Frank; Duboy, Alberto; Simhan, Jay; et al.
Penile prosthetic surgery is an effective treatment for men with erectile dysfunction. Cancellation of surgery is disruptive and costly to patients, physicians, and the healthcare system. This pilot study sought to analyze surgery cancellations and implement a video-based patient education program to decrease surgery noncompletion. Baseline penile prosthetic surgery completion, rescheduling, and cancellation rates among consecutively scheduled surgeries were determined using a national cohort. Selected prosthetic surgeons then implemented Vidscrip, a video-based patient education program. Prerecorded videos were delivered via text message 14 days, 7 days, and 1 day preoperatively, as well as 1 day postoperatively. Subsequent analysis determined noncompletion rates, reasons for noncompletion, surgeon volume, and video utilization. Two-hundred twenty-six surgeries were scheduled in the baseline cohort; 141 were completed, and 85 were rescheduled or canceled. Among the intervention cohort, 290 patients completed, 7 rescheduled, and 37 canceled surgery. After program implementation, the surgery noncompletion rate was reduced compared to baseline (13.2% vs. 37.6%, p < .05), corresponding to a number needed to treat of 4.1. When stratified by surgeon volume, there was no difference in noncompletion rate (>20 cases vs. ≤20 cases: 8.20% vs. 32.0%, p = .35). Video utilization was widely variable among practices (median viewing time 58.6 min, IQR 5.09–113). Penile prosthetic surgery is frequently rescheduled or canceled. Implementing a video-based patient education program reduces surgery noncompletion, improving efficiency and quality of care. Wider implementation is needed to validate these findings, while cost-effectiveness analyses may further support their broad adoption.